South America Climate During the 1970–2001 Pacific Decadal Oscillation Phases Based on Different Reanalysis Datasets - Silva, Maria Elisa Siqueira; Silva, Carlos Batista; Ambrizzi, Tercio; Drumond, Anita; Patucci, Natália Nunes (Frontiers in Earth Science, 2020)
In this paper circulation and precipitation climate patterns over the South America domain obtained from NCEP-NCAR reanalysis I, JRA-55 and ERA-40 reanalysis datasets were intercompared within the period 1970-2001 in order to verify their climatic association with the Pacific Decadal Oscillation, PDO. Although all three datasets show similar climatic patterns during each PDO phase, they show distinct intensities for circulation and precipitation variables. The mean low frequency flow propagation over the South Pacific during negative and positive PDO phases reaches central-eastern South America (SA) with opposite signals, contributing to modulate the local climate. During the negative PDO phases, the northerly flow over South America is intensified, while during the positive phase it is weakened. NCEP-NCAR reanalysis I, in comparison with JRA-55 and ERA-40 values, always indicates the strongest signal for circulation and precipitation variables. NCEP-NCAR reanalysis I meridional wind at the low-level jet area is about 5% and 12% larger than the respective JRA-55 and the ERA-40 values. For the positive and negative PDO phases, only NCEP-NCAR and ERA-40 high level zonal wind anomalies show, respectively, divergent (positive PDO) and convergent (negative PDO) patterns close to 140o W at equatorial latitudes of the Pacific Ocean. This one indicates distinct representations of the positioning of Walker cells in the three reanalysis datasets. GPCC dataset, NCEP-NCAR, JRA-55 and ERA-40 reanalysis, show, in general, the dipole precipitation pattern over eastern of South America, with signs of changes between the central-eastern and southeastern areas during PDO reversal phases. Over the central-eastern South American region, NCEP-NCAR precipitation is, on average, 57 % larger than GPCC values, and, respectively, 35% and 46% larger than JRA-55 and ERA-40 values. Observed patterns of anomalies for different PDO phases appear in all reanalysis data sets, leading us to conclude that the physical meaning is independent from the datasets. Even considering the JRA-55 climate signal over the SA associated with the PDO influence as the weakest one, the ability of JRA-55 to calculate monthly precipitation provided the highest linear correlation coefficient values in tropical areas, leading us to consider this data set as the most reliable for the studied area.